ANALYSIS PERFORMANCE IN SOFTWARE DEFINED NETWORK (SDN) USING ARUBA VAN CONTROLLER - Rifqi Fauzan; Syariful Ikhwan; Jafaruddin Gusti Amri Ginting (Jurnal Informatika: Jurnal Pengembangan IT, 2020)
SDN technology is a new architecture in the network that separates the control plan from the data plan. Aruba VAN Controller provides centralized control in a network architecture that runs on the OpenFlow protocol. This study conducted an SDN network simulation using the Aruba VAN Controller by applying the Narmox Spear application to simplify network configuration. IP addressing with DHCP server, for testing scenarios using UDP protocol packet delivery with packets sent at 1000 Bytes, the number of packets sent is 100 packets/s, then given background traffic variations of 50 Mbps, 100 Mbps, 150 Mbps and 200 Mbps to networks that have two different link bandwidth values as a comparison for analyzing the results of testing the QoS parameters, which are 100 Mbps and 200 Mbps. The test results are obtained when background traffic exceeds the link bandwidth capacity, the resulting throughput will be smaller on the destination side by 485.64 Kb/s, delay increases by 240.21 ms, then for jitter by 2.48 ms, resulting in overload resulting in packet loss of 37.41%. However, when background traffic increases and does not exceed the specified link bandwidth capacity, the overall QoS parameter value is generated in the good category, namely throughput of 774.42 Kb/s, delay of 0.41 ms, jitter of 0.37 ms and packet loss of 0.00%. Keyword - SDN, Aruba VAN Controller, OpenFlow, DHCP, UDP, QoS